Left atrial size derived by non-contrast cardiac computed tomography and risk of incident atrial fibrillation. (25th November 2020) - Fredgart, M.H; Lindholt, J.S; Brandes, A; Steffensen, F.H; Frost, L; Lambrechtsen, J; Karon, M; Busk, M; Urbonaviciene, G; Egstrup, K; Diederichsen, A.C.P
Abstract: Introduction: Left atrial (LA) size is an independent predictor of cardiovascular outcome. While performing non-contrast computed tomography (NCCT), LA size is readily available, and a single cross-section area provides a accurate estimate of LA enlargement. Purpose: The purpose of this study was to examine if enlarged LA measured by a NCCT scan was an independent risk factor of subsequent atrial fibrillation or flutter (AF). Methods: The Cardiovascular Screening Trial; a population-based multicenter randomized screening trial, consisting primarily of men aged 60–74 years were randomly allocated (1:2) for screening. NCCT was performed and LA area was manually traced in a single axial slice excluding the pulmonary veins at mitral valve level. LA size was indexed to body surface area. Indexed LA area was divided into five categories (defined by standard deviations). Hospital admission due to AF were identified using data from the National Patient Registry using ICD-10 codes (DI48-DI489). Results: Between 2014 and 2019, 14, 986 participants were enrolled, of these 13, 410 without known AF were eligible for follow-up. During 2.3±1.0 years of follow-up 301 developed incident AF, corresponding to an incidence rate of 10.0 per 1, 000 person-years. Figure 1 shows the Kaplan-Meier of incident AF stratified by categories of LA (p<0.0001). A very large LA was associated with a four-fold higher risk of incident AF in the fully adjusted analysis (HR (95% CI): 4.0 (2.6–5.8), p<0.0001), and a two-fold higher risk by a large LA (HR (95% CI): 2.0 (1.5–2.6), p<0.0001) (Table 1). Conclusion: An enlarged LA area measured by NCCT was associated with a two to four-fold higher risk of incident AF. The prognostic use of LA area provides an individual risk assessment during NCCT for other purposes. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): This work was supported by the University of Southern Denmark and the Region of Southern Denmark.